Journalistic investigation on Ukrainian television - Harmatiy, O. V. (Українська академія друкарства, 2017)
The article deals with the varieties, subjects and tendencies of the functioning of investigative projects in modern television media. Journalistic investigations on leading Ukrainian TV channels, such as 1+1, ICTV, Channel 5, New Channel, UA: First ar being studied. As journalistic investigations are actively developing on the Ukrainian TV in the context of democratization of society, so its influence is also growing. It was established that the thematic priorities of investigatory materials are: the fight against corruption, social and historical issues. TV investigations attract attention of the audience to problems and form public opinion, thus becoming a catalyst for the civil society development. It has been concluded that the effectiveness of the indirect influence of journalistic investigative projects is higher, than their direct influence. As important tendencies of investigative journalism have been determined the orientation of the media to direct dialogue with the audience for identification and research of socio-important issues and apparition of media investigation groups in the public sector. Based on such characteristics of Ukrainian investigative projects, the desire of the media to serve as means of informing and means of influence is intensified. Досліджено різновиди, тематика, тенденції функціонування розслідувальних проектів в сучасних телевізійних медіа. Розглядаються і журналістські розслідування на провідних українських телеканалах: “1+1”, “ICTV”, “5 канал”, “Новий канал”, “UA:Перший”. Журналістське розслідування активно розвивається на українському ТБ в контексті демократизації суспільства і паралельно зростає його впливовість. Встановлено, що тематичними пріоритетами розслідувальних матеріалів є боротьба з корупцією, соціальна й історична тематика. ТБ-розслідування привертають увагу аудиторії до проблем, формують громадську думку і таким чином стають каталізатором розвитку громадянського суспільства. Зроблено висновок про більшу ефективність опосередкованого впливу журналістських розслідувальних проектів, аніж їх безпосередню результативність. Важливими тенденціями розслідувальної журналістики визначено орієнтацію медіа на безпосередній діалог з аудиторією для виявлення і дослідження суспільно важливих проблем, вихід медійних розслідувальних груп у громадський сектор. На базі таких характеристик українських розслідувальних проектів посилюється прагнення медіа бути як засобом інформування, так і засобом впливу.
Журналістське розслідування на українському телебаченні
Keywords: journalistic investigation; investigative journalism; investigative project; TV investigation; журналістське розслідування; розслідувальна журналістика; розслідувальний проект; телевізійне розслідування; [ 007 : [ 070 : 304] : 654.19 (477)